Development of Rapid Temporal Processing and Its Impact on Literacy Skills in Primary School Children. Issue 4 (20th December 2013) - Steinbrink, Claudia; Zimmer, Karin; Lachmann, Thomas; Dirichs, Martin; Kammer, Thomas
<x xml:space="preserve">Abstract</x> In a longitudinal study, auditory and visual temporal order thresholds (TOTs) were investigated in primary school children (N = 236; mean age at first data point = 6;7) at the beginning of Grade 1 and the end of Grade 2 to test whether rapid temporal processing abilities predict reading and spelling at the end of Grades 1 and 2. Auditory and visual TOTs differed but showed comparable developmental trajectories over 20 months. Visual TOTs were not predictive of literacy measures; auditory TOTs in Grade 1 were the best predictor. Interestingly, they were related to spelling in Grade 2 while auditory TOTs in Grade 2 were not, suggesting that rapid auditory processing abilities have a causal influence on literacy development.